2007
DOI: 10.15562/jdmfs.v6i1.132
|View full text |Cite
|
Sign up to set email alerts
|

Keterbatasan radiografi panoramik dalam pengukuran ketidaksimetrisan mandibula

Abstract: Panoramic radiography is a technique to yield face structure photo including bone ofmaxilla, mandible and supporting structures like maxilla antrum, nasal fossa, TMJ,procesus styloideus, and os. hyoid. Panoramic radiography is also used to evaluateasymmetrical of face. Growth and development of head is similar to the growth anddevelopment of body in general. The skeletal morphology can be disturbed by internaldisorder of TMJ and degenerative joint disease as short ramus, a sharp angle of mandible,and also cran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Radiograf panoramik menampilkan struktur fasial yang termasuk diantaranya adalah rahang atas, rahang bawah, dan persendian temporomandibular. (11,12,13) Secara radiografi, foramen mental dapat terlihat antara bulat atau oval, daerah radiolusen yang tidak beraturan sebagian ataupun pada seluruh tepinya. (14,15,16) Berdasarkan hasil penelitian Prabodha dan Nanayakkara (2006) didapatkan kesimpulan bahwa terdapat variasi yang signifikan pada posisi foramen mental berdasarkan usia.…”
Section: Pendahuluanunclassified
“…Radiograf panoramik menampilkan struktur fasial yang termasuk diantaranya adalah rahang atas, rahang bawah, dan persendian temporomandibular. (11,12,13) Secara radiografi, foramen mental dapat terlihat antara bulat atau oval, daerah radiolusen yang tidak beraturan sebagian ataupun pada seluruh tepinya. (14,15,16) Berdasarkan hasil penelitian Prabodha dan Nanayakkara (2006) didapatkan kesimpulan bahwa terdapat variasi yang signifikan pada posisi foramen mental berdasarkan usia.…”
Section: Pendahuluanunclassified
“…Mental index can be used to detect osteoporosis because previous studies showed that depletion of the mandibular cortical thickness below the mental foramen has a significant correlation with low BMD or osteoporosis. 7 This study uses panoramic radiography as a research medium because it displays the entire image in a single film. Panoramic radiography was selected in the framework of early osteoporosis because the examination is easier to perform, more equipment is available and inspection costs are more affordable.…”
Section: Original Researchmentioning
confidence: 99%
“…Osteoporosis not only related to menopause but also related to other factors such as smoking, small body posture, less activity, sun light radiation, drug decreased bone mass, low-intake calcium, caffeine and alcohol consumption, and diabetes mellitus disease. [4][5][6] Gold standard in diagnosing osteoporosis is Bone Mineral Density (BMD) because it is the best predictor to bone fracture; commonly measured with Dual Energy X-ray Absorptiometry (DXA) assays which stated as the best equipment detecting osteoporosis recently. [7][8][9] The problem in Indonesia that the availability of DXA hardware is limited to a big hospital and its uneasy to conduct a special diagnosis using DXA.…”
Section: Introductionmentioning
confidence: 99%